Short-Term Effect of Rice Straw Management on Organic Carbon and Soil CN Ratio - Handayani, Ida Ayu Kusuma Tri; Sulastri, Ni Nyoman; Arthawan, I Gusti Ketut Arya; Wijaya, I Made Anom Sutrisna (Jurnal BETA (Biosistem dan Teknik Pertanian), 2025)
The annual rice planting cycle produced 6.73 tons of dry straw per hectare. Rice straw had beneficial nutrients for plants, but farmers often burned or buried it to reduce waste and enhance soil fertility. Because straw was hard to decompose, additional decomposers like bacteria were needed. This study aimed to investigate the short-term impact of rice straw management on soil organic carbon (C-organic) and the C/N ratio. The experimental design used was Nested Design. The study involved three straw management treatments: burning (BR), straw incorporation without EM4 addition (S0), and straw incorporation with EM4 addition (S1). Laboratory analysis was conducted on the C-organic and C/N ratio parameters. Differences in soil parameters observed before and after straw management treatments were analyzed using the Wilcoxon Signed Rank Test. The analysis showed an increase in C-organic after treatment: 29.7% for burning, 10.9% for straw incorporation, and 10.2% for straw incorporation with EM4. The rise in C-organic after straw management treatments is due to the mineralization of soil organic matter. This mineralization is indicated by average C/N values below 20, although the C/N ratio after burning increased by 56% and after straw incorporation with EM4 increased by 0.35%. The average C/N ratios from all treatments ranged from 9.1 to 16.8. In the short term, all three straw treatments can increase organic carbon and C/N ratios below 20.